Coaxial GaAs-AlGaAs core-multishell nanowire lasers with epitaxial gain control - Stettner, T.; Zimmermann, P.; Loitsch, B.; Döblinger, M.; Regler, A.; Mayer, B.; Winnerl, J.; Matich, S.; Riedl, H.; Kaniber, M.; Abstreiter, G.; Koblmüller, G.; et al. (Applied physics letters, 2016)
We demonstrate the growth and single-mode lasing operation of GaAs-AlGaAs core-multishell nanowires (NW) with radial single and multiple GaAs quantum wells (QWs) as active gain media. When subject to optical pumping lasing emission with distinct s-shaped input-output characteristics, linewidth narrowing and emission energies associated with the confined QWs are observed. Comparing the low temperature performance of QW NW laser structures having 7 coaxial QWs with a nominally identical structure having only a single QW shows that the threshold power density reduces several-fold, down to values as low as ∼2.4 kW/cm2 for the multiple QW NW laser. This confirms that the individual radial QWs are electronically weakly coupled and that epitaxial design can be used to optimize the gain characteristics of the devices. Temperature-dependent investigations show that lasing prevails up to 300 K, opening promising new avenues for efficient III–V semiconductor NW lasers with embedded low-dimensional gain media.